Accelerometry measurements of sprint kayaks: The coaches' new tool - Robinson, M. G.; Holt, L.E.; Pelham Waverley, T. W.; Furneaux Dalhousie, K. (International Journal of Coaching Science, 2011)
In flatwater paddling competition, optimal physiological power, effective technique and the correct race strategy are essential for peak performance. However, other important factors are the matching of equipment with athlete and placement order in crews. In this study, an in-board accelerometer measured craft dynamics of the sprint racing K-1 and K-4 with various combinations of international class paddlers. Acceleration values were greater on the right when compared to the left for the K-1 paddler. In the K-4 trails, crew 3 demonstrated greater accelerations, achieved faster times over the measured distance with the fewest number of strokes when compared with crews 1 and 2. Acceleration data sets were consistent with personal observations and video analysis conducted by Olympic coaches. This study clearly demonstrated that acceleration data sets can augment the analysis of performance, match equipment with athlete, identify stroke technique faults, and in the crew selection process.